Teaching Philosophy as Basic Course a Personal Reﬂection - Mikhael Dua (Respons: Jurnal Etika Sosial, 2015)
Abstrak: Mengajar flsafat sebagai sebuah mata kuliah dasar di sebuah Universitas merupakan sebuah pengalaman yang khas yang tidak dimiliki oleh para dosen yang sudah in line dengan pengembangan keilmuannya. Tulisan ini mencoba mengungkapkan pengalaman penulis tentang keterlibatannya dalam menangani flsafat ilmu pengetahuan, etika dan flsafat yang menyentuh masalah keilmuan dan kebudayaan. Dalam rangka peneerdasan kehidupan bangsa, flsafat memiliki target-target yang jarang diperhatikan oleh pengelolah ilmu pengetahuan. Melalui mata kuliah tersebut di atas, flsafat dapat membantu pengembangan nalar keilmuan, membawa ilmuwan bergumul dengan masalah moral dan kebudayaan. Dan yang paling penting, flsafat dapat membuka mata setiap orang untuk membangun peradaban yang lebih demokratis dengan nalarnya yang kritis.Kata Kunci: Filsafat, ilmu pengetahuan, kesadaran moral, demokrasi, Pusat Pengembangan Etika Atma Jaya, Panca Sila.Abstract: Teaching philosophy as basic subject for students of different schools of the same university aims to prepare them with the discipline of abstract but universal and correct thinking. Te experience about the job by philosophy teachers is quite different from theachers who do teach science according to their specialities in different schools of the same university. Tis essay reﬂects a personal experience of the writer in teaching philosophy of science, ethics, and other branch of philosophy according to the specifc requirement of different schools in the same university. In connection with the end of a university formation, philosophy is granted to prepare students with both intellectual and moral expertise but often philosophical design for this end is not incorporated in science. Te discrepancy between philosophy and science has become the concern of philosophy teacher to attract multidisciplinary curriculum design to keep university faithful to its main goal which is to make society becomes more rational and democratic.Key Words: Philosophy, science, moral consciousness, democracy, Atma Jaya Center for Philosophy and Ethics, Pancasila